Comparative study on coagulant, defibrinating, fibrinolytic and fibrinogenolytic activities of Costa Rican crotaline snake venoms and their neutralization by a polyvalent antivenom - Gené, José Antonio (1989)
The coagulant, defibrinating, fibrino lytic and fibrinogenolytic activities of venoms from ten species of Costa Rican crotaline snakes were studied, together with the neutralization of these effects by a polyvalent antivenom. The venoms of Bothrops asper, B. schlegelii, B. nummifer, B. godmani, Lachesis muta and Crotalus durissus induced a coagulant effect in vitro, and all of them, with the exception of B. nummifer, also induced defibrination in vivo. The four non-coagulant venoms (B. lateralis, B. ophryomegas, B. nasuta and B. picadoi) induced a degradation of the alpha (A) chain of fibrinogen, thereby inhibiting coagulation. However, they did not induce defibrination upon i.v. injection. All of the venoms showed fibrinolytic activity in vitro. Polyvalent antivenom was effective in the neutralization of coagulant, defibrinating, fibrinolytic and fibrinogenolytic activities of these venoms, with the exception of coagulant effect induced by C. durissus venom. Since only three venoms are used in the immunization of horses, these results demonstrate the high degree of immunological cross reactivity between components affecting coagulation in Costa Rican crotaline snake venoms.